Enhanced Antibacterial Activity of Melt Processed Poly(propylene) Ag and Cu Nanocomposites by Argon Plasma Treatment. Issue 4 (24th February 2014) - España‐Sánchez, Beatriz L.; Ávila‐Orta, Carlos A.; Padilla‐Vaca, Felipe; Neira‐Velázquez, María G.; González‐Morones, Pablo; Rodríguez‐González, José A.; Hernández‐Hernández, Ernesto; Rangel‐Serrano, Ángeles; Barriga‐C., Enrique Díaz; Yate, Luis; Ziolo, Ronald F.
<x xml:space="preserve">Abstract</x> Argon surface plasma treatment (APT) of poly(propylene)/silver (PP/Ag) and poly(propylene)/copper (PP/Cu) nanocomposite improves their antibacterial properties against pathogenic bacteria. Dispersions of PP/Ag and PP/Cu nanocomposites were prepared by sonication assisted melt mixing 0.05, 0.5, and 5 w/w% metal nanoparticle/polymer compositions, and then melt casted to form films that were surface treated with argon plasma. Scanning electron and atomic force microscopy showed that APT increase the surface roughness and the exposed nanoparticles. Also, APT produced implanted oxygen and nitrogen species as demonstrated by XPS analysis and enhanced the surface wettability. Antibacterial activity (AA) against S. aureus and P. aeruginosa of the plasma treated NC films was significantly increased in all conditions tested such as NP loading and interaction time; copper NCs were more effective than silver NCs. Surface activation of the PP/Ag and PP/Cu NC films by APT is a viable technique to increase the antibacterial activity of nanocomposites, an important issue in medical and health care applications.<inline-graphic xlink:href="ark:/27927/pgg59wdq97x" content-type="ppap201300152-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />